The Problems of Using Google Classroom as a Learning Tool for Islamic Religious Education in the Covid-19 Era - Adi Saputra; Karmi Kostia Leza Intan Permata; Suhirman Suhirman (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: Problematika Penggunaan Google Classroom Sebagai Sarana Pembelajaran Pendidikan Agama Islam Pada Era Covid-19Tujuan penelitian ini untuk mengetahui problematika penggunaan Google Classroom sebagai sarana pembelajaran di era Covid-19 pada mata pelajaran PAI kelas 11 di SMA Negeri 6 Kota Bengkulu dan mengetahui upaya menghadapi problematikanya. Jenis penelitiannya adalah kualitatif, dengan pendekatan deskriptif. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Informan berjumlah 12 orang yaitu 1 orang kepala sekolah SMA, 2 orang guru Pendidikan Agama Islam, dan 9 orang siswa-siswi. Hasil penelitian menunjukkan bahwa problematikanya adalah terdapat sarana yang kurang mendukung seperti jaringan yang tidak stabil; siswa yang tidak mempunyai smartphone dan laptop; masih banyak guru yang belum mahir menggunakan teknologi dan sosial media untuk pembelajaran jarak jauh; siswa yang tidak mengerti cara menggunakan teknologi untuk pembelajaran. Upaya dalam menghadapi problematikanya adalah pihak sekolah memberikan pelatihan menggunakan Google Classroom sebelum kegiatan belajar dilaksanakan; menyediakan kuota internet untuk belajar. Dewan guru selalu memberikan motivasi belajar kepada peserta didik. Guru juga bergabung di seluruh grup Whatsapp kelas dan aplikasi Google Clasroom sehingga dapat mengawasi aktivitas belajar online.Abstract: The Problems of Using Google Classroom as a Learning Tool for Islamic Religious Education in the Covid-19 EraThe purpose of this study was to find out the problems of using Google Classroom as a learning tool in the Covid-19 era in 11th grade Islamic Lesson at Public High School 6 Bengkulu City and to find out how to deal with the problems. This type of research is qualitative, with a descriptive approach. Data collection techniques using observation, interviews and documentation. There were 12 informants, namely 1 high school principal, 2 Islamic Religious Education teachers, and 9 students. The results of the study indicate that the problem is that there are facilities that are not supported, such as an unstable network; students who do not have smartphones and laptops; there are still many teachers who are not proficient in using technology and social media for distance learning; students who do not understand how to use technology for learning. Efforts to deal with the problem are that the school provides training using Google Classroom before learning activities are carried out; provide internet quota for studying. The teacher council always provides learning motivation to students. Teachers also join all class Whatsapp groups and the Google Classroom application so they can monitor online learning activities.